Workforce-management system boosts efficiency at Sysco. Issue 6 (10th August 2015) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Observes how two companies are benefiting from a new workforce-management system. Design/methodology/approach – Examines how new software is helping the Sysco Group and Scan Computers. Findings – Shows how the two companies are better able to track each employee's working hours and absences including sickness and time-off, to make things easier when it comes to things like payroll and holiday entitlement. Practical implications – Reveals that the biometric employee-attendance software uses fingerprint identification to track employees' whereabouts throughout the working day. The software can cope with any type of work pattern and calculate overtime using its script engine. Originality/value – Explains that, with so many companies opting for flexible working hours or rotational shifts, the software makes these easier to put into practice.